Analisis Pengaruh Tingkat Literasi Koperasi dan Pengalaman Organisasi Terhadap Minat Mahasiswa Menjadi Anggota Koperasi - Manihuruk, Frido Evindey; Oktania, Ainur; Silfani, Dwi; Matondang, Khairani Alawiyah (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study analyses the influence of cooperative literacy and organizational experience on students' interest in becoming cooperative members, with a case study of UNIMED Faculty of Economics students. The low participation of Generation Z in cooperatives and the fact that 68.9% of FE UNIMED students have never joined a cooperative prompted this study. Quantitative methods were used with data collection through an online questionnaire to 178 respondents (a sample of 3,558 population). Multiple regression analysis tested the effect of independent variables (cooperative literacy and organizational experience) on interest in becoming a cooperative member. The results show that cooperative literacy has a positive effect (sig. 0.003; β = 0.260), and organizational experience also has a positive and significant effect (sig. 0.000; β = 0.759). F test (246,631 > 3.05) and Adj. R² (0.829) proved that the two variables together had a significant effect of 82.9%. The findings conclude that in addition to improving literacy, organizational experience is a key factor in driving student interest. Research recommendations include integrating cooperative education into the curriculum and increasing organizational opportunities for students.